2020
DOI: 10.1016/j.bja.2020.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Personalised haemodynamic management targeting baseline cardiac index in high-risk patients undergoing major abdominal surgery: a randomised single-centre clinical trial

Abstract: Background: Despite several clinical trials on haemodynamic therapy, the optimal intraoperative haemodynamic management for high-risk patients undergoing major abdominal surgery remains unclear. We tested the hypothesis that personalised haemodynamic management targeting each individual's baseline cardiac index at rest reduces postoperative morbidity. Methods: In this single-centre trial, 188 high-risk patients undergoing major abdominal surgery were randomised to either routine management or personalised haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 52 publications
1
34
0
2
Order By: Relevance
“…28,29 Futier et al 11 also reported that "individualized" arterial pressure management resulted in less postoperative organ dysfunction. More recently, Nicklas et al 12 demonstrated that individualizing hemodynamic management by using patient baseline cardiac index value as a target to guide fluid administration resulted in fewer postoperative complications. However, adoption of these strategies by clinicians has been slow, and even if used during surgery, results may be limited because of poor protocol compliance.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Futier et al 11 also reported that "individualized" arterial pressure management resulted in less postoperative organ dysfunction. More recently, Nicklas et al 12 demonstrated that individualizing hemodynamic management by using patient baseline cardiac index value as a target to guide fluid administration resulted in fewer postoperative complications. However, adoption of these strategies by clinicians has been slow, and even if used during surgery, results may be limited because of poor protocol compliance.…”
Section: Discussionmentioning
confidence: 99%
“…These thresholds were determined intraoperatively, post-CPB, by the intraoperative team (surgery and anesthesiology) utilizing a variety of inputs including: patient's comorbidity, pre-CPB and post-CPB HD data, echocardiography, cerebral oximetry, urine output, CPB duration and surgical variables. The concept of individualized hemodynamic management using patient's baseline cardiac index in high-risk abdominal surgical patients had demonstrated to reduce postoperative complications [26]. And It is the authors' belief, that identifying individualized targets was a key component of impacting patient improvement and supported the high compliance of GDT protocol adoption.…”
Section: Discussionmentioning
confidence: 96%
“…51 In this regard, noninvasive pulse wave analysis systems enable clinicians to determine baseline CO before surgery (e.g., the day before surgery on the ward). In the Targeting Preoperatively Assessed Personal Cardiac Index in Major Abdominal Surgery Patients (TAPIR) trial, 52 noninvasive pulse wave analysis (CNAP system) was used to determine the individual patient's baseline cardiac index the day before surgery. In patients assigned to personalized management, clinicians strove to maintain this baseline cardiac index during surgery-where cardiac index was measured using minimally invasive internally calibrated pulse wave analysis (ProAQT/ Pulsioflex system)-by using fluids and dobutamine based on a goal-directed therapy algorithm.…”
Section: Pulse Wave Analysis In Perioperative Medicinementioning
confidence: 99%